(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Pre-eclampsia is a significant cause of maternal and neonatal morbidity and mortality worldwide, affecting 2–10% of pregnancies. Early-onset pre-eclampsia (EO-PE) and late-onset pre-eclampsia (LO-PE) may have distinct pathophysiological mechanisms and clinical outcomes. Aim: To compare the fetomaternal outcomes between early-onset and late-onset pre-eclampsia in patients treated at LD Hospital, Government Medical College, Srinagar. Methods: This prospective study was conducted from July 2021 to December 2022, including 300 women with pre-eclampsia (≥20 weeks of gestation), divided equally into EO-PE (n=150) and LO-PE (n=150). Pre-eclampsia was defined according to the ACOG 2018 criteria. Maternal outcomes (eclampsia, HELLP syndrome, abruption, postpartum hemorrhage, maternal mortality) and perinatal outcomes (preterm birth, low birth weight, stillbirth, Apgar score, NICU admission, neonatal death, umbilical artery Doppler changes) were compared between groups. Results: The mean gestational age at diagnosis was 29 weeks in EO-PE and 35 weeks in LO-PE. The EO-PE group showed significantly higher rates of primigravida (73.3% vs 46.7%, p=0.00001). Maternal complications, including eclampsia (9.3% vs 5.3%), HELLP syndrome (7.3% vs 4.6%), and abruption (6% vs 2.6%), were higher in EO-PE, though not statistically significant. Perinatal outcomes were significantly worse in EO-PE: preterm birth (50% vs 10%), low birth weight (66.7% vs 40%), stillbirth (14% vs 6%, p=0.0003), NICU admission (60% vs 20%, p<0.0001), neonatal death (24% vs 6%, p<0.0001), and abnormal umbilical artery Doppler (32% vs 8%, p<0.0001). Cesarean section rate was significantly higher in EO-PE (80% vs 60%, p<0.00001). Conclusion: Early-onset pre-eclampsia is associated with significantly worse maternal and perinatal outcomes compared to late-onset pre-eclampsia. Early identification, close surveillance, timely intervention, and referral are essential to reduce complications in EO-PE patients.